Some problems of legal regulation of customs procedures in the Customs Union (Journal of actual problems of jurisprudence, 2019)
According to the goal of scientific work carried out the identification of problems of legal regulation of customsprocedures in the Customs Union. During the study, familiarized with the legal framework of the Customs Union andthe analysis of changes in connection with the adoption of the Customs Code of the Customs Union. The analysisconsidered the advantages and disadvantages of changes of the Customs Code of the Customs Union.Key words: the Customs procedure, the Customs Union, the Customs Code of the Customs Union, Commission of theCustoms Union.